PELATIHAN PEMBUATAN MODUL SEJARAH LOKAL TERINTEGRASI MATERI PELAJARAN SEJARAH DI SMA BAGI GURU SEJARAH DI KECAMATAN RENGAT BARAT KABUPATEN INDRAGIRI HULU - Fikri, Asyrul; Isjoni, Isjoni; Barkara, Refli Surya; Yuliantoro, Yuliantoro; Negara, Chandra Perwira; Warsani, Henki (Unri Conference Series: Community Engagement, 2024)
So far, history learning has only focused on the national events of a nation. In fact, local history is an integral part of national history. Local history is able to provide a sense of pride and a deep understanding of regional culture. For this reason, an integrated local history module is needed so that students' understanding is better. The creation of the module is carried out through 3 stages, namely preparation, implementation and evaluation. The resulting product is in the form of a local history module integrated with history lessons. The content in the module can be filled with local history material of Riau Province and iconic events in the area. In addition, modules can be filled with local terms that are close to the student's environment. Local historical elements are very important, because they can understand the struggle of ancestors in navigating their times and there are local wisdom values of a region. This service was carried out in Indragiri Hulu Regency because it was in accordance with the analysis of needs and its strategic location in developing local welfare modules.